3
$\begingroup$

$\newcommand{\betabold}{\boldsymbol{\beta}} \newcommand{\xbold}{\boldsymbol{x}} \newcommand{\ebold}{\boldsymbol{e}}$ For $\betabold\in \mathbb R^3$, with $0<|\betabold|<1$, let us denote the Lorentz boost with velocity $\betabold$ by $$ L^{\betabold}(t, \xbold):=\Big(\gamma t-\gamma \betabold\cdot \xbold, \xbold_\bot +\gamma \xbold_{\parallel}-\gamma\betabold t\Big), \quad \text{where }\ \gamma:=\frac{1}{\sqrt{1-\beta^2}}.$$ Here $\xbold_\parallel:=\frac{\xbold\cdot\betabold}{\beta^2}\betabold$ is the component of $\xbold$ in the direction of $\betabold$, and $\xbold_\bot:=\xbold-\xbold_\parallel$. (The speed of light is normalized to $1$).

Does there exist a spatial rotation $R$ and $\alpha_1, \alpha_2, \alpha_3\in(-1, 1)$ such that $$ L^\betabold = L^{\alpha_1\ebold_1}L^{\alpha_2\ebold_2}L^{\alpha_3\ebold_3}R\quad ?$$

$\endgroup$
  • 2
    $\begingroup$ A rotation can move any unit vector to coincide with any axis. So there exists a rotation which rotates $\mathbf \beta $ to the $\mathbf e_3$ axis. So yes; just look for such a rotation and then choose $\alpha_3 =|\mathbf \beta|$ and $\alpha_2=\alpha_1 = 0$. $\endgroup$ – Dwagg Oct 6 '18 at 14:41
  • 1
    $\begingroup$ @Dwagg: Don't you need a second rotation after the boost? $\endgroup$ – Giuseppe Negro Oct 6 '18 at 15:15
  • 1
    $\begingroup$ The commutator of two boost generators is a rotation generator. And you have $L^{\vec\varphi}=\exp(\mathrm{i}\vec\varphi\cdot \vec B)$, where $\vec B=(B_x,B_y,B_z)$ is a 3-tuple of boost generators. Your question is then if $L^{\vec\varphi}=L^{\alpha_1e_1}L^{\alpha_2e_2}L^{\alpha_3e_3}R$ for some appropriate $\alpha_i$ and $R$. The answer is yes because of the Baker-Campbell-Hausdorff formula. $\endgroup$ – user178876 Oct 6 '18 at 17:15
  • 1
    $\begingroup$ Related : General matrix Lorentz transformation. By intuition there are infinitely many solutions. $\endgroup$ – Frobenius Oct 6 '18 at 18:39
  • 1
    $\begingroup$ Elaborating an answer to your question first results show that my intuition about infinitely many solutions is false. I could prove that for given $\:\boldsymbol{\beta}\:$ there exists one and only one triad $\:\left(\alpha_1,\alpha_2,\alpha_3\right)\:$ and consequently one rotation R satisfying your equation. $\endgroup$ – Frobenius Oct 10 '18 at 9:35
4
$\begingroup$

\begin{equation} \mathrm{L}\left(\boldsymbol{\beta}\right) =\mathrm{R}^{\boldsymbol{-1}}\cdot\mathrm{L}_3\left(\alpha_3\right)\cdot\mathrm{L}_2\left(\alpha_2\right)\cdot\mathrm{L}_1\left(\alpha_1\right) \tag{a}\label{a} \end{equation} \begin{equation} \alpha_1 =\beta_1\,, \quad \alpha_2 =\dfrac{\beta_2}{\sqrt{1-\beta^2_1}}\,, \quad \alpha_3 =\dfrac{\beta_3}{\sqrt{1-\left(\beta^2_1+\beta^2_2\right)}} \tag{b}\label{b} \end{equation} \begin{equation} \mathrm{R}=\text{space rotation} \tag{c}\label{c} \end{equation} $==================================================$

enter image description here

Figure-01 3D

From Figure 01 :

Lorentz Transformation from $\:\mathrm{S}\boldsymbol{\equiv} \{xyz\omega, \omega\boldsymbol{=}ct\}\:$ to $\:\mathrm{S_1}\boldsymbol{\equiv} \{x_1y_1z_1\omega_1, \omega_1\boldsymbol{=}ct_1\}\:$ \begin{equation} \begin{bmatrix} x_1\\ y_1\\ z_1\\ \omega_1 \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \hphantom{-}\cosh\!\xi & \hphantom{-}0 & \hphantom{-}0 &-\sinh\!\xi \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & 0\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ -\sinh\!\xi & \hphantom{-} 0 & \hphantom{-} 0 &\hphantom{-}\cosh\!\xi \end{bmatrix} \begin{bmatrix} x\\ y\\ z\\ \omega \end{bmatrix} \,, \quad \tanh\!\xi\boldsymbol{=}\alpha_1\boldsymbol{=}\dfrac{u_1}{c} \tag{01}\label{01} \end{equation} or \begin{equation} \mathbf{W}_1\boldsymbol{=}\mathrm{L_1}\mathbf{W}\,, \qquad \mathrm{L_1}\boldsymbol{=} \begin{bmatrix} \hphantom{-}\cosh\!\xi & \hphantom{-}0 & \hphantom{-}0 &-\sinh\!\xi \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & 0\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ -\sinh\!\xi & \hphantom{-} 0 & \hphantom{-} 0 &\hphantom{-}\cosh\!\xi \end{bmatrix} \tag{02}\label{02} \end{equation}

Lorentz Transformation from $\:\mathrm{S_1}\boldsymbol{\equiv} \{x_1y_1z_1\omega_1, \omega_1\boldsymbol{=}ct_1\}\:$ to $\:\mathrm{S_2}\boldsymbol{\equiv} \{x_2y_2z_2\omega_2, \omega_2\boldsymbol{=}ct_2\}\:$ \begin{equation} \begin{bmatrix} x_2\\ y_2\\ z_2\\ \omega_2 \end{bmatrix} \boldsymbol{=} \begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}\cosh\!\eta & \hphantom{-} 0 & -\sinh\!\eta\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ 0 & -\sinh\!\eta & \hphantom{-} 0 &\hphantom{-}\cosh\!\eta \end{bmatrix} \begin{bmatrix} x_1\\ y_1\\ z_1\\ \omega_1 \end{bmatrix} \,, \quad \tanh\!\eta\boldsymbol{=}\alpha_2\boldsymbol{=}\dfrac{u_2}{c} \tag{03}\label{03} \end{equation} or \begin{equation} \mathbf{W}_2\boldsymbol{=}\mathrm{L_2}\mathbf{W}_1\,, \qquad \mathrm{L_2}\boldsymbol{=} \begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}\cosh\!\eta & \hphantom{-} 0 & -\sinh\!\eta\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ 0 & -\sinh\!\eta & \hphantom{-} 0 &\hphantom{-}\cosh\!\eta \end{bmatrix} \tag{04}\label{04} \end{equation}

Lorentz Transformation from $\:\mathrm{S_2}\boldsymbol{\equiv} \{x_2y_2z_2\omega_2, \omega_2\boldsymbol{=}ct_2\}\:$ to $\:\mathrm{S_3}\boldsymbol{\equiv}\{x_3y_3z_3\omega_3, \omega_3\boldsymbol{=}ct_3\}\:$ \begin{equation} \begin{bmatrix} x_3\\ y_3\\ z_3\\ \omega_3 \end{bmatrix} \boldsymbol{=} \begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & \hphantom{-}0\\ 0 & \hphantom{-}0 & \hphantom{-}\cosh\!\zeta & -\sinh\!\zeta\\ 0 & \hphantom{-}0 & -\sinh\!\zeta &\hphantom{-}\cosh\!\zeta \end{bmatrix} \begin{bmatrix} x_2\\ y_2\\ z_2\\ \omega_2 \end{bmatrix} \,, \quad \tanh\!\zeta\boldsymbol{=}\alpha_3\boldsymbol{=}\dfrac{u_3}{c} \tag{05}\label{05} \end{equation} or \begin{equation} \mathbf{W}_3\boldsymbol{=}\mathrm{L_3}\mathbf{W}_2\,, \qquad \mathrm{L_3}\boldsymbol{=} \begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & \hphantom{-}0\\ 0 & \hphantom{-}0 & \hphantom{-}\cosh\!\zeta & -\sinh\!\zeta\\ 0 & \hphantom{-}0 & -\sinh\!\zeta &\hphantom{-}\cosh\!\zeta \end{bmatrix} \tag{06}\label{06} \end{equation}

Note that because of the Standard Configurations the matrices $\:\mathrm{L_1}, \mathrm{L_2},\mathrm{L_3}\:$ are real symmetric.

From equations \eqref{02},\eqref{04} and \eqref{06} we have \begin{equation} \mathbf{W}_3\boldsymbol{=}\mathrm{L}_3\mathbf{W}_2\boldsymbol{=}\mathrm{L}_3\mathrm{L}_2\mathbf{W}_1\boldsymbol{=}\mathrm{L}_3\mathrm{L}_2\mathrm{L}_1\mathbf{W} \quad \boldsymbol{\Longrightarrow} \quad \mathbf{W}_3\boldsymbol{=}\Lambda\,\mathbf{W} \tag{07}\label{07} \end{equation} where $\:\Lambda\:$ the composition of the three Lorentz Transformations $\:\mathrm{L_1}, \mathrm{L_2},\mathrm{L_3}\:$ \begin{align} &\Lambda\boldsymbol{=}\mathrm{L}_3\mathrm{L}_2\mathrm{L}_1\boldsymbol{=} \nonumber\\ &\begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & \hphantom{-}0\\ 0 & \hphantom{-}0 & \hphantom{-}\cosh\!\zeta & -\sinh\!\zeta\\ 0 & \hphantom{-}0 & -\sinh\!\zeta &\hphantom{-}\cosh\!\zeta \end{bmatrix} \begin{bmatrix} 1 & \hphantom{-}0 & \hphantom{-}0 &\hphantom{-}0 \\ 0 & \hphantom{-}\cosh\!\eta & \hphantom{-} 0 & -\sinh\!\eta\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ 0 & -\sinh\!\eta & \hphantom{-} 0 &\hphantom{-}\cosh\!\eta \end{bmatrix} \begin{bmatrix} \hphantom{-}\cosh\!\xi & \hphantom{-}0 & \hphantom{-}0 &-\sinh\!\xi \\ 0 & \hphantom{-}1 & \hphantom{-} 0 & 0\\ 0 & \hphantom{-} 0 & \hphantom{-} 1 & 0\\ -\sinh\!\xi & \hphantom{-} 0 & \hphantom{-} 0 &\hphantom{-}\cosh\!\xi \end{bmatrix} \tag{08}\label{08} \end{align} that is \begin{equation} \Lambda\boldsymbol{=}\mathrm{L}_3\mathrm{L}_2\mathrm{L}_1\boldsymbol{=} \begin{bmatrix} \hphantom{-}\cosh\!\xi & \hphantom{-}0 & \hphantom{-}0 &-\sinh\!\xi\\ \hphantom{-}\sinh\!\eta\sinh\!\xi & \hphantom{-}\cosh\!\eta & \hphantom{-}0 & -\sinh\!\eta\cosh\!\xi\\ \hphantom{-}\sinh\!\zeta\cosh\!\eta\sinh\!\xi & \hphantom{-}\sinh\!\zeta\sinh\!\eta &\hphantom{-} \cosh\!\zeta & -\sinh\!\zeta\cosh\!\eta\cosh\!\xi\\ -\cosh\!\zeta\cosh\!\eta\sinh\!\xi & -\cosh\!\zeta\sinh\!\eta & -\sinh\!\zeta &\hphantom{-}\cosh\!\zeta\cosh\!\eta\cosh\!\xi \end{bmatrix} \tag{09}\label{09} \end{equation} The Lorentz Transformation matrix $\:\Lambda\:$ is not symmetric, so the systems $\:\mathrm{S},\mathrm{S_3}\:$ are not in the Standard configuration. But it's reasonable to suppose that \begin{equation} \Lambda=\mathrm{R}\cdot\mathrm{L} \tag{10}\label{10} \end{equation} where $\:\mathrm{L}\:$ is the symmetric Lorentz Transformation matrix from $\:\mathrm{S}\:$ to an intermediate system $\:\mathrm{S'}_3\:$ in Standard configuration to it and co-moving with $\:\mathrm{S}_3\:$, while $\:\mathrm{R}\:$ is a purely spatial transformation between $\:\mathrm{S'}_3\:$ and $\:\mathrm{S}_3$.

Now, our target would be to express the symmetric Lorentz Transformation matrix $\:\mathrm{L}\:$ in terms of the rapidities $\:\xi,\eta,\zeta\:$ since from \eqref{10}
\begin{equation} \mathrm{R}\boldsymbol{=}\Lambda\cdot\mathrm{L}^{\boldsymbol{-1}} \tag{11}\label{11} \end{equation}

The Lorentz Transformation matrix $\:\mathrm{L}\:$, from $\:\mathrm{S}\:$ to the intermediate system $\:\mathrm{S'_3}\:$ in Standard Configuration to it, is : \begin{equation} \mathrm{L}\left(\boldsymbol{\upsilon} \right)\boldsymbol{=} \begin{bmatrix} 1\!+\!\left(\gamma\!-\!1\right)\!\mathrm{n}^{2}_{x} & \left(\gamma\!-\!1\right)\!\mathrm{n}_{x}\mathrm{n}_{y} & \left(\gamma\!-\!1\right)\!\mathrm{n}_{x}\mathrm{n}_{z} & \!-\dfrac{\gamma\upsilon_{x}}{c} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \left(\gamma\!-\!1\right)\!\mathrm{n}_{y}\mathrm{n}_{x} & 1\!+\!\left(\gamma\!-\!1\right)\!\mathrm{n}^{2}_{y} &\left(\gamma\!-\!1\right)\!\mathrm{n}_{y}\mathrm{n}_{z} & \!-\dfrac{\gamma\upsilon_{y}}{c} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \left(\gamma\!-\!1\right)\!\mathrm{n}_{z}\mathrm{n}_{x} & \left(\gamma\!-\!1\right)\!\mathrm{n}_{z}\mathrm{n}_{y} & 1\!+\!\left(\gamma\!-\!1\right)\!\mathrm{n}^{2}_{z} & \!-\dfrac{\gamma\upsilon_{z}}{c} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \!-\dfrac{\gamma\upsilon_{x}}{c} & \!-\dfrac{\gamma\upsilon_{y}}{c} &\!-\dfrac{\gamma\upsilon_{z}}{c} & \gamma \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{12}\label{12} \end{equation} In \eqref{12} \begin{align} \dfrac{\boldsymbol{\upsilon}}{c} & \boldsymbol{=} \left(\dfrac{\upsilon_{x}}{c},\dfrac{\upsilon_{y}}{c},\dfrac{\upsilon_{z}}{c}\right)\boldsymbol{=}\left(\tanh\!\xi,\dfrac{\tanh\!\eta}{\cosh\!\xi},\dfrac{\tanh\!\zeta}{\cosh\!\xi\cosh\!\eta}\right)\equiv \boldsymbol{\beta}\boldsymbol{=} \left(\beta_1,\beta_2,\beta_3,\right) \tag{13.1}\label{13.1}\\ \left(\dfrac{\upsilon}{c}\right)^{2} & \boldsymbol{=} \left(\dfrac{\upsilon_{x}}{c}\right)^{2}+\left(\dfrac{\upsilon_{y}}{c}\right)^{2}+\left(\dfrac{\upsilon_{z}}{c}\right)^{2} \boldsymbol{=}1 \boldsymbol{-}\left(\dfrac{1}{\cosh\!\xi\cosh\!\eta\cosh\!\zeta}\right)^{2}=\dfrac{\gamma^{2}\!-\!1}{\gamma^{2}} \tag{13.2}\label{13.2}\\ \gamma & \boldsymbol{=} \left(\!1\!-\!\frac{\upsilon^{2}}{c^{2}}\right)^{-\frac12}\boldsymbol{=} \cosh\!\xi\cosh\!\eta\cosh\!\zeta \boldsymbol{=}\gamma_1\gamma_2\gamma_3 \tag{13.3}\label{13.3}\\ \mathbf{n} & = \left(\mathrm{n}_{x},\mathrm{n}_{y},\mathrm{n}_{z}\right) \boldsymbol{=}\dfrac{\boldsymbol{\upsilon}/c}{\upsilon/c}\boldsymbol{=}\dfrac{\left(\sinh\!\xi\cosh\!\eta\cosh\!\zeta ,\sinh\!\eta\cosh\!\zeta,\sinh\!\zeta\right)}{\sqrt{\cosh^2\!\xi\cosh^2\!\eta\cosh^2\!\zeta-1}} \tag{13.4}\label{13.4} \end{align} where $\:\boldsymbol{\upsilon}\:$ is the velocity vector of the origin $\:\mathrm{O'}_{\!\!3}\left(\equiv \mathrm{O}_{3}\right)\:$ with respect to $\:\mathrm{S}$(1), $\:\mathbf{n}\:$ the unit vector along $\:\boldsymbol{\upsilon}\:$ and $\:\gamma\:$ the corresponding $\:\gamma-$factor.

So the matrix $\:\mathrm{L}\left(\boldsymbol{\upsilon} \right)\:$ of equation \eqref{12} as function of the rapidities $\:\xi,\eta,\zeta\:$ is(2) \begin{align} &\mathrm{L}\left(\boldsymbol{\upsilon} \right)\boldsymbol{=}\mathrm{L}\left(\xi,\eta,\zeta \right)\boldsymbol{=} \nonumber\\ &\begin{bmatrix} 1\!+\!\dfrac{\sinh^{2}\!\xi\cosh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} &\dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \!\boldsymbol{-} \sinh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } &\dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \!\boldsymbol{-} \sinh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } & \!\boldsymbol{-}\sinh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \!\boldsymbol{-}\sinh\!\xi\cosh\!\eta\cosh\!\zeta & \!\boldsymbol{-}\sinh\!\eta\cosh\!\zeta &\!\boldsymbol{-}\sinh\!\zeta & \cosh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{14}\label{14} \end{align} while \begin{align} &\mathrm{L}^{\boldsymbol{-1}}\left(\boldsymbol{\upsilon} \right)\boldsymbol{=}\mathrm{L}\left(\boldsymbol{-}\boldsymbol{\upsilon} \right)\boldsymbol{=}\mathrm{L}\left(\boldsymbol{-}\xi,\boldsymbol{-}\eta,\boldsymbol{-}\zeta \right)\boldsymbol{=} \nonumber\\ &\begin{bmatrix} 1\!+\!\dfrac{\sinh^{2}\!\xi\cosh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} &\dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \! \sinh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } &\dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \! \sinh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } & \!\sinh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \!\sinh\!\xi\cosh\!\eta\cosh\!\zeta & \!\sinh\!\eta\cosh\!\zeta &\!\sinh\!\zeta & \cosh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{15}\label{15} \end{align}

From equations \eqref{09},\eqref{11} and \eqref{15} \begin{align} &\mathrm{R}\boldsymbol{=}\Lambda\cdot\mathrm{L}^{\boldsymbol{-1}}\boldsymbol{=} \nonumber\\ &\begin{bmatrix} \hphantom{-}\cosh\!\xi & \hphantom{-}0 & \hphantom{-}0 &-\sinh\!\xi\vphantom{\dfrac{a}{b}}\\ \hphantom{-}\sinh\!\eta\sinh\!\xi & \hphantom{-}\cosh\!\eta & \hphantom{-}0 & -\sinh\!\eta\cosh\!\xi\vphantom{\dfrac{a}{b}}\\ \hphantom{-}\sinh\!\zeta\cosh\!\eta\sinh\!\xi & \hphantom{-}\sinh\!\zeta\sinh\!\eta &\hphantom{-} \cosh\!\zeta & -\sinh\!\zeta\cosh\!\eta\cosh\!\xi\vphantom{\dfrac{a}{b}}\\ -\cosh\!\zeta\cosh\!\eta\sinh\!\xi & -\cosh\!\zeta\sinh\!\eta & -\sinh\!\zeta &\hphantom{-}\cosh\!\zeta\cosh\!\eta\cosh\!\xi\vphantom{\dfrac{a}{b}} \end{bmatrix} \nonumber\\ &\begin{bmatrix} 1\!+\!\dfrac{\sinh^{2}\!\xi\cosh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} &\dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \! \sinh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\eta\cosh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } &\dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \! \sinh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\eta\cosh\!\zeta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 1\!+\!\dfrac{\sinh^2\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta } & \!\sinh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \!\sinh\!\xi\cosh\!\eta\cosh\!\zeta & \!\sinh\!\eta\cosh\!\zeta &\!\sinh\!\zeta & \cosh\!\xi\cosh\!\eta\cosh\!\zeta \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix}\boldsymbol{=} \nonumber\\ &\begin{bmatrix} \dfrac{\cosh\!\xi\!+\!\cosh\!\eta\cosh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\sinh\!\xi\sinh\!\eta\cosh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\sinh\!\xi\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 0 \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\sinh\!\eta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\eta} & \hphantom{\boldsymbol{-}}\dfrac{\cosh\!\eta\!+\!\cosh\!\zeta\cosh\!\xi}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\cosh\!\xi\sinh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 0 \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\eta} & \dfrac{\cosh\!\zeta\!+\!\cosh\!\xi\cosh\!\eta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & 0 \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ 0 & 0 & 0 & 1 \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{16}\label{16} \end{align} \begin{equation} \mathcal R= \begin{bmatrix} \dfrac{\cosh\!\xi\!+\!\cosh\!\eta\cosh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\sinh\!\xi\sinh\!\eta\cosh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\sinh\!\xi\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\sinh\!\eta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\eta} & \hphantom{\boldsymbol{-}}\dfrac{\cosh\!\eta\!+\!\cosh\!\zeta\cosh\!\xi}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \boldsymbol{-}\dfrac{\cosh\!\xi\sinh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ \dfrac{\sinh\!\xi\cosh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} & \dfrac{\sinh\!\eta\sinh\!\zeta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\eta} & \dfrac{\cosh\!\zeta\!+\!\cosh\!\xi\cosh\!\eta}{1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta} \vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{17}\label{17} \end{equation} \begin{equation} \mathcal R= \begin{bmatrix} \cos\theta+(1-\cos\theta)\mathrm{m}_{x}^2 & (1-\cos\theta)\mathrm{m}_{x}\mathrm{m}_{y}+\sin\theta\mathrm{m}_{z} & (1-\cos\theta)\mathrm{m}_{x}\mathrm{m}_{z}-\sin\theta\mathrm{m}_{y}\vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ (1-\cos\theta)\mathrm{m}_{y}\mathrm{m}_{x}-\sin\theta\mathrm{m}_{z}& \cos\theta+(1-\cos\theta)\mathrm{m}_{y}^2 & (1-\cos\theta)\mathrm{m}_{y}\mathrm{m}_{z}+\sin\theta\mathrm{m}_{x}\vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}}\\ (1-\cos\theta)\mathrm{m}_{z}\mathrm{m}_{x}+\sin\theta\mathrm{m}_{y} & (1-\cos\theta)\mathrm{m}_{z}\mathrm{m}_{y}-\sin\theta\mathrm{m}_{x} & \cos\theta+(1-\cos\theta)\mathrm{m}_{z}^2\vphantom{\dfrac{\dfrac{}{}}{\tfrac{}{}}} \end{bmatrix} \tag{18}\label{18} \end{equation} \begin{align} & 2\cos\theta+1=\mathrm{trace}(\mathcal R)= \nonumber\\ &\dfrac{\left(\cosh\!\xi\!+\!\cosh\!\eta\!+\!\cosh\!\zeta\right)\!+\!\left(\cosh\!\xi\cosh\!\eta\!+\!\cosh\!\eta\!\cosh\!\zeta\!+\!\cosh\!\zeta\cosh\!\xi\right)}{\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \nonumber\\ &\dfrac{\left(1\!+\!\cosh\!\xi\right)\left(1\!+\!\cosh\!\eta\right)\left(1\!+\!\cosh\!\zeta\right)-\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)}{\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \tag{19}\label{19} \end{align} \begin{equation} \cos\theta=\dfrac{\left(1\!+\!\cosh\!\xi\right)\left(1\!+\!\cosh\!\eta\right)\left(1\!+\!\cosh\!\zeta\right)-2\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)}{2\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \tag{20}\label{20} \end{equation} \begin{equation} \cos\theta=\dfrac{\left(1\!+\!\gamma_1\right)\left(1\!+\!\gamma_2\right)\left(1\!+\!\gamma_3\right)-2\left(1\!+\!\gamma_1\gamma_2\gamma_3\right)}{2\left(1\!+\!\gamma_1\gamma_2\gamma_3\right)}\,,\quad \gamma_{\jmath}=\left(1\!-\!\alpha_{\jmath}\right)^{\boldsymbol{-\frac12}}\:\: \vphantom{\dfrac{\dfrac{a}{b}}{\dfrac{c}{d}}} \tag{21}\label{21} \end{equation} \begin{align} \sin\theta\,\mathrm{m}_{x} & = \boldsymbol{-}\dfrac{\left(1\!+\!\cosh\!\xi\right)\sinh\!\eta\sinh\!\zeta}{2\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \tag{22.1}\label{22.1}\\ \sin\theta\,\mathrm{m}_{y} & = \boldsymbol{+}\dfrac{\left(1\!+\!\cosh\!\eta\right)\sinh\!\zeta\sinh\!\xi}{2\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \tag{22.2}\label{22.2}\\ \sin\theta\,\mathrm{m}_{z} & = \boldsymbol{-}\dfrac{\left(1\!+\!\cosh\!\zeta\right)\sinh\!\eta\sinh\!\xi}{2\left(1\!+\!\cosh\!\xi\cosh\!\eta\cosh\!\zeta\right)} \tag{22.3}\label{22.3} \end{align} \begin{align} \sin\theta & =\dfrac{\sqrt{\left(1\!+\!\gamma_1\right)^2\left(\gamma_2^2\!-\!1\right)\left(\gamma_3^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_2\right)^2\left(\gamma_3^2\!-\!1\right)\left(\gamma_1^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_3\right)^2\left(\gamma_1^2\!-\!1\right)\left(\gamma_2^2\!-\!1\right)}}{2\left(1\!+\!\gamma_1\gamma_2\gamma_3\right)} \nonumber\\ \gamma_{\jmath} & =\left(1\!-\!\alpha_{\jmath}\right)^{\boldsymbol{-\frac12}}\,,\quad \theta\in [0,\pi] \tag{23}\label{23} \end{align} \begin{align} \tan\theta & =\dfrac{\sqrt{\left(1\!+\!\gamma_1\right)^2\left(\gamma_2^2\!-\!1\right)\left(\gamma_3^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_2\right)^2\left(\gamma_3^2\!-\!1\right)\left(\gamma_1^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_3\right)^2\left(\gamma_1^2\!-\!1\right)\left(\gamma_2^2\!-\!1\right)}}{\left(1\!+\!\gamma_1\right)\left(1\!+\!\gamma_2\right)\left(1\!+\!\gamma_3\right)-2\left(1\!+\!\gamma_1\gamma_2\gamma_3\right)} \nonumber\\ \gamma_{\jmath} & =\left(1\!-\!\alpha_{\jmath}\right)^{\boldsymbol{-\frac12}}\,,\quad \theta\in [0,\pi] \tag{24}\label{24} \end{align} \begin{align} \mathbf{m} & =\dfrac{\biggl[\left(1\!+\!\gamma_1\right)\left(\gamma_2^2\!-\!1\right)^{\boldsymbol{\frac12}}\left(\gamma_3^2\!-\!1\right)^{\boldsymbol{\frac12}}\:\boldsymbol{,}\:\left(1\!+\!\gamma_2\right)\left(\gamma_3^2\!-\!1\right)^{\boldsymbol{\frac12}}\left(\gamma_1^2\!-\!1\right)^{\boldsymbol{\frac12}}\:\boldsymbol{,}\:\left(1\!+\!\gamma_3\right)^2\left(\gamma_1^2\!-\!1\right)^{\boldsymbol{\frac12}}\left(\gamma_2^2\!-\!1\right)^{\boldsymbol{\frac12}}\biggr]}{\sqrt{\left(1\!+\!\gamma_1\right)^2\left(\gamma_2^2\!-\!1\right)\left(\gamma_3^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_2\right)^2\left(\gamma_3^2\!-\!1\right)\left(\gamma_1^2\!-\!1\right)\!+\!\left(1\!+\!\gamma_3\right)^2\left(\gamma_1^2\!-\!1\right)\left(\gamma_2^2\!-\!1\right)}} \nonumber\\ \gamma_{\jmath} & =\left(1\!-\!\alpha_{\jmath}\right)^{\boldsymbol{-\frac12}}\,,\quad \theta\in [0,\pi] \tag{25}\label{25} \end{align}

$==================================================$

enter image description here Figure-02 3D


(1) see APPENDIX C - Relativistic addition of velocities


(2) see APPENDIX B - The matrix L


(3) Constructing $\:\boldsymbol{\alpha}\:$ from $\:\boldsymbol{\beta}\:$


| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Impressive. That's lots of work. It will take a while for me to digest it, but thank you very much for your time. $\endgroup$ – Giuseppe Negro Oct 12 '18 at 16:14
  • $\begingroup$ @Frobenius Nice! One little question: What software/package are you using for the graph? $\endgroup$ – J C Oct 13 '18 at 0:25
  • $\begingroup$ @J C : GeoGebra. One of its advantages is inserting equations in $\LaTeX$. $\endgroup$ – Frobenius Oct 13 '18 at 5:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.